Cannabis use in first episode psychosis: Meta-analysis of prevalence, and the time course of initiation and continued use. (March 2016) - Myles, Hannah; Myles, Nicholas; Large, Matthew
Objectives: Cannabis use is prevalent among people with first episode psychosis and the epidemiology of its use in early psychosis is unclear. We performed a meta-analysis of observational studies to determine; (1) the interval between age at initiation of cannabis use and age at onset of first episode psychosis, (2) the prevalence of cannabis use at time of first episode psychosis, and (3) the odds of continuing cannabis following treatment for first episode psychosis. Data sources: Search of electronic databases MEDLINE, EMBASE, PsycINFO, Web of Science and CINAHL for English-language papers using search terms (psychosis OR schizophrenia) AND (cannabis OR marijuana) IN (title OR keyword OR abstract), current to October 2014. Study selection: Studies were included if they reported on prevalence of current cannabis use in first episode psychosis cohorts. A total of 37 samples were included for meta-analysis. Data extraction: Rates of cannabis use in each sample were extracted to determine prevalence estimates. The age at initiation of regular cannabis and age at onset of psychosis were used to determine the length of cannabis use preceding psychosis. Prevalence estimates at first episode psychosis and various time points of follow-up following first episode psychosis were analysed to determine odds ratio of continuing cannabis use. Data synthesis was performed using random-effects meta-analyses. Results: The pooled estimate for the interval between initiation of regular cannabis use and age at onset of psychosis was 6.3 years (10 samples, standardised mean difference = 1.56, 95% confidence interval = [1.40, 1.72]). The estimated prevalence of cannabis use at first episode psychosis was 33.7% (35 samples, 95% confidence interval = [31%, 39%]). Odds of continued cannabis use between 6 months and 10 years following first episode psychosis was 0.56 (19 samples, 95% confidence interval = [0.40, 0.79]).